Penerapan Metode Natural Language Processing (NLP) Pada Question Answering System Untuk Media Informasi Mahasiswa Universitas Bhayangkara Jakarta Raya - Nurfiyah; Nurfan Ramadhandi (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Information is one of the key words in the era of globalization, in life activities it requires information that is useful for everyone. Submission of information to students at Bhayangkara University is delivered in several ways, namely, wall magazines, faculty whatsapp groups, and academic information systems for information related to teaching and learning activities. Some of these methods are still considered to be less effective in some cases that the authors found in the field. For example faculty staff often find it difficult to reply to all student questions in the faculty whatapps group, this is an obstacle for students to obtain accurate information In order to meet information needs at Bhayangkara University, Greater Jakarta it is considered necessary to implement atechnology chatbot to produce accurate information about information they need. the method used is Natural Languge Processing (NLP) which focuses on natural language processing. the result of implementing chatbot thisis being able to complete the work on faculty staff to help reply to questions posed by students through thegroup whatsapp facultyand the information obtained by students is much faster because there is no need to wait for replies from faculty staff.